Discovery and characterization of N-(1, 3-dialkyl-1H-indazol-6-yl)-1H-pyrazolo[4, 3-b]pyridin-3-amine scaffold as mGlu4 positive allosteric modulators that mitigate CYP1A2 induction liability. Issue 15 (15th August 2018) - Engers, Darren W.; Bollinger, Sean R.; Engers, Julie L.; Panarese, Joseph D.; Breiner, Megan M.; Gregro, Alison; Blobaum, Anna L.; Bronson, Joanne J.; Wu, Yong-Jin; Macor, John E.; Rodriguez, Alice L.; Zamorano, Rocio; et al.
Graphical abstract: Highlights: A new indazole based mGlu4 PAM scaffold is reported. This scaffold showed excellent potency, selectivity and brain penetration. A detailed SAR analysis around the CYP induction issue that has plagued previous scaffolds. Abstract: Previous reports from our laboratory disclosed the structure and activity of a novel 1 H -pyrazolo[4, 3- b ]pyridine-3-amine scaffold (VU8506 ) which showed excellent potency, selectivity and in vivo efficacy in preclinical rodent models of Parkinson's disease. Unfortunately, this compound suffered from significant CYP1A2 induction as measured through upstream AhR activation (125-fold) and thus was precluded from further advancement in chronic studies. Herein, we report a new scaffold developed recently which was systematically studied in order to mitigate the CYP1A2 liabilities presented in the earlier scaffolds. We have identified a novel structure that maintains the potency and selectivity of other mGlu4 PAMs, leading to 9i (hmGlu4 EC50 = 43 nM; AhR activation = 2.3-fold).